173k views
0 votes
Solve by using the Quadratic Formula3u^2 + 7u- 3= 0

1 Answer

2 votes

SOLUTION

Given the question in the image, the following are the solution steps to answer the question.

STEP 1: Write the quadratic equation


3u^2+7u-3=0

STEP 2: Write the needed terms


\begin{gathered} By\text{ comparison with standard quadratic equation of the form:} \\ ax^2+bx+c=0 \\ a=3,b=7,c=-3 \end{gathered}

STEP 3: Write the quadratic formula


u_(1,2)=(-b\pm√(b^2-4ac))/(2a)

STEP 4: Substitute the values into the formula


u_(1,2)=(-7\pm√(7^2-4\cdot3\cdot(-3)))/(2\cdot3)

STEP 5: Simplify:


u_(1,2)=(-7\pm√(49+36))/(6)=(-7\pm√(85))/(6)

STEP 6: Separate the solutions


u_1=(-7+√(85))/(6),u_2=(-7-√(85))/(6)

STEP 7: Simplify:


\begin{gathered} u_1=0.369924076\approx0.37 \\ u_2=-2.70325741\approx-2.70 \end{gathered}

Hence, the values of u are:


\begin{gathered} 0.37 \\ -2.70 \end{gathered}

User Peter Friend
by
4.6k points